2018
DOI: 10.1038/s41561-018-0199-0
|View full text |Cite
|
Sign up to set email alerts
|

High temperatures in the terrestrial mid-latitudes during the early Palaeogene

Abstract: The early Paleogene (56-48 Myr) provides valuable information about the Earth's climate system in an equilibrium high pCO2 world. High ocean temperatures have been reconstructed for this greenhouse period, but land temperature estimates have been cooler than expected. This mismatch between marine and terrestrial temperatures has been difficult to reconcile. Here we present terrestrial temperature estimates from a newly-calibrated brGDGTbased paleothermometer in ancient lignites (fossilized peat). Our results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 54 publications
10
78
0
Order By: Relevance
“…However, such an offset is not unprecedented. In the Cenozoic, TEX 86 generally agrees well with the trends and absolute temperatures reconstructed from alkenones (e.g., U K′ 37 ), foraminiferal δ 18 O and Mg/Ca ratios, and clumped isotopes (Δ 47 ) of carbonates, though commonly showing a slight offset to warmer SSTs (Bijl et al, 2009(Bijl et al, , 2010Castañeda et al, 2010;Douglas et al, 2014;Hollis et al, 2009Hollis et al, , 2012Huguet et al, 2006;Keating-Bitonti et al, 2011;Lopes dos Santos et al, 2013;Menzel et al, 2006;Meyer et al, 2018;Naafs et al, 2018;Pearson et al, 2007;Richey et al, 2011;Shintani et al, 2011;Woelders et al, 2018;Zachos et al, 2006). The causality of these higher temperatures remains unresolved but has been attributed by many authors to a summer bias of the Thaumarchaeota or a winter bias of the other proxies.…”
Section: Absolute Sst Value Comparison From Site 511 and Implicationssupporting
confidence: 64%
See 1 more Smart Citation
“…However, such an offset is not unprecedented. In the Cenozoic, TEX 86 generally agrees well with the trends and absolute temperatures reconstructed from alkenones (e.g., U K′ 37 ), foraminiferal δ 18 O and Mg/Ca ratios, and clumped isotopes (Δ 47 ) of carbonates, though commonly showing a slight offset to warmer SSTs (Bijl et al, 2009(Bijl et al, , 2010Castañeda et al, 2010;Douglas et al, 2014;Hollis et al, 2009Hollis et al, , 2012Huguet et al, 2006;Keating-Bitonti et al, 2011;Lopes dos Santos et al, 2013;Menzel et al, 2006;Meyer et al, 2018;Naafs et al, 2018;Pearson et al, 2007;Richey et al, 2011;Shintani et al, 2011;Woelders et al, 2018;Zachos et al, 2006). The causality of these higher temperatures remains unresolved but has been attributed by many authors to a summer bias of the Thaumarchaeota or a winter bias of the other proxies.…”
Section: Absolute Sst Value Comparison From Site 511 and Implicationssupporting
confidence: 64%
“…A long-standing problem in paleoclimatology is the discrepancy between proxy data and model simulations for high latitudes in a greenhouse world. Proxy records indicate equable conditions and reduced latitudinal temperature gradients (e.g., Amiot et al, 2004;Hollis et al, 2009;Huber et al, 1995Huber et al, , 2002Keating-Bitonti et al, 2011;Naafs et al, 2018;Pearson et al, 2007;Sinninghe Damsté et al, 2010), whereas models indicate cooler polar conditions and steeper latitudinal gradients (Barron, 1987;Huber & Sloan, 1999, 2001Bice et al, 2006;Huber & Caballero, 2011;Lunt et al, 2012Lunt et al, , 2016Tabor et al, 2016;Upchurch et al, 2015).…”
Section: 1029/2018pa003546mentioning
confidence: 99%
“…11. The identification of foraminifera was carried out by following the works of Murray and Wright (1974), Singh and Kalia (1970), Kalia (1978), Loeblich Jr. and Tappan (2015) and Pearson et al (2005). The paleoenvironment and paleodepositional analysis has been carried out by using foraminiferal morphogroups (Nagy, 1992;Preece et al, 1999;Nigam et al, 2007;Reolid et al, 2008;Singh et al, 2015).…”
Section: Foraminiferal Analysismentioning
confidence: 99%
“…Recent work has shown that brGDGTs are also produced in situ in the marine water column and in the hosting marine sediments (Sinninghe Damsté, 2016; Weijers et al, 2014), in rivers and in lakes (Naeher et al, 2014;Weber et al, 2015). To illustrate this, we plot the relative abundance of the tetra-, penta-and hexamethylated brGDGTs of the published early Paleogene data from five sites together with the modern mineral soil and peat data (Naafs et al, 2017a, b) and early Paleogene data from lignites (Naafs et al, 2018a, b), following the approach of Sinninghe Damsté (2016) (Fig. 5a).…”
Section: Weaknesses Of Brgdgt Paleothermometrymentioning
confidence: 99%
“…The same is true for the available CO 2 proxies. Over the past few years, researchers associated with the DeepMIP project have made great advances in recovering paleotemperature records from poorly sampled regions, in both high (Frieling et al, 2014;Hollis et al, 2015;Schoon et al, 2015;Hines et al, 2017) and low latitudes (Inglis et al, 2015;Frieling et al, 2017Cramwinckel et al, 2018;Evans et al, 2018a;Naafs et al, 2018a). Several of these studies have applied new methodologies to deep-sea cores collected over 20 years ago Inglis et al, 2015;Cramwinckel et al, 2018).…”
Section: Conclusion and Priorities For New Data Gatheringmentioning
confidence: 99%